A NEW FUNCTION OF PERSONAL DATA IN THE LIGHT OF THE CONTRACT FOR THE SUPPLY OF DIGITAL CONTENT AND DIGITAL SERVICES - Midorović, Sloboda D; Sekulić, Miloš B. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
The paper addresses solutions of the recently adopted Digital Content Directive (abbreviated: DCD) with the focus on its major novelty being the possibility of a consumer to provide his personal data in lieu of a price in return for a digital content or a digital service. Though this social phenomenon has been known in practice for quite some time, the DCD is the first instrument of the European Union (abbreviated: EU) that accepted such reality by laying down a legal framework tailor-made to such contractual performance. Prior to its adoption, the main concern was how to reconcile two aspects of personal data: the fact that the right to the protection of personal data presents a fundamental human right, on one hand, and a rising use of such data as an object of contractual performance in the digital environment, on the other hand. The need to conciliate these two dimensions of personal data led to some revisions of the European Commission’s Proposal of the DCD. These changes led, inter alia, to a clear reference in the DCD to the already existing regime for the protection of personal data at the EU level epitomised in the General Data Protection Regulation (abbreviated: GDPR). Apart from relevant solutions of the DCD, the paper also examines arguments favouring the DCD implementation in Serbian legal system, proposing at the same time the most appropriate piece of legislation for that.